Effect of Interfaces on Small, Starved Marine Bacteria - Kjelleberg, Staffan (1982)
The copiotrophic marine Vibrio sp. strain DW1, shown previously in batch culture to increase in numbers at the onset of starvation and then to form viable small cells with low endogenous respiration, appears to have a survival advantage at interfaces. Vibrio sp. strain DW1 behaved differently at interfaces compared with the aqueous phase under starvation conditions: (i) small cells were observed at an air-water interface without nutrients, (ii) nutrients added to the air-water interface quickly produced larger cells at the surface, (iii) motility persisted many hours longer at the solid-water interface of a dialysis membrane in a microchamber at the onset of starvation, and (iv) regrowth and division at the solid-liquid interface occurred quickly and at nutrient concentrations too low to permit growth in the aqueous phase. It was concluded that, if small starved cells from copiotrophic bacteria can reach an interface, additional survival mechanisms become available to them: (i) interfaces constitute areas of favorable nutrient conditions, and (ii) interfaces lacking a sufficient amount of nutrient, nevertheless, trigger cells to become smaller, thus increasing their surface/volume ratio and the packing density.